Facile regioselective decomposition of tosylhydrazones: an application towards the synthesis of alpha-lipoic acid - Chavan, Subhash P.; Kale, R. R.; Pasupathy, K. (Synlett, 2005)
A facile regioselective decomposition of tosylhydrazones using NaOH as a base in refluxing isopropyl alcohol is described. This finding has been Successfully applied towards the synthesis of (&PLUSMN;)-α-lipoic acid (1).
Keywords: alpha-lipoic acid; Olefins; Regioselectivity; tosylhydrazones

First enantiospecific synthesis of (+)-beta-herbertenol - Chavan, Subhash P.; Thakkar, M.; Kharul, Rajendra K.; Pathak, A. B.; Bhosekar, Gaurav V.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
The first enantiospecific synthesis of (+)-beta-herbertenol, from naturally occurring R-(+)-citronellal, employing Taber's diazo decomposition protocol as the key step, is described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: citronellal; diazo decomposition; enantiospecific

First enantiospecific synthesis of (-)-parvifoline and (-)-curcuquinone - Chavan, Subhash P.; Thakkar, Mahesh; Jogdand, Ganesh F.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2006)
The first enantiospecific synthesis of (-)-parvifoline, employing ring-closing metathesis as the key step, and (-)-curcuquinone from naturally occurring (R)-(+)-citronellal is described.

Facile total synthesis of (+/-)-alpha-cuparenone employing diallylation and RCM as key steps - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
A short and concise total synthesis of alpha-cuparenone employing one-pot diallylation and RCM as the key steps is described. (c) 2006 Elsevier Ltd. All rights reserved.

First enantiospecific synthesis of (-)-heritol: absolute configuration determination - Chavan, Subhash P.; Thakkar, Mahesh; Kalkote, Uttam R. (Tetrahedron Letters, 2007)
The first enantiospecific synthesis of (-)-heritol, from naturally occurring (R)-(+)-citronellal and confirmation of its absolute configuration, is described. (c) 2006 Elsevier Ltd. All rights reserved.

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Formal synthesis of (+/-)-camptothecin via tricyclic lactone as key synthon - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
Formal synthesis of (+/-)-camptothecin via CDE tricyclic lactone employing tandem Michael addition, Dieckmann condensation and addition-elimination reaction as key steps starting from glycinate is described. (C) 2010 Elsevier Ltd. All rights reserved.

Formal synthesis of (-)-stemoamide using a useful epimerization at C-8 - Chavan, Subhash P.; Harale, Kishor R.; Puranik, Vedavati G.; Gawade, Rupesh L. (Tetrahedron Letters, 2012)
The formal synthesis of (-)-stemoamide was achieved starting from L-pyroglutamic acid. The key steps used are the allylation using BF3 center dot OEt2, ring closing metathesis, allylic oxidation and a novel epimerization at C8. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allylation; Allylic oxidation; Pyroglutamic acid; Ring closing metathesis; Stemoamide

Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid

Formal synthesis of brivaracetam: a key to construct the pyrrolidone scaffold using Pd-catalyzed oxidative cyclization and ring-closing metathesis reaction - Chavan, Subhash P.; Kawale, Sanket A.; Chavan, Prakash N. (Tetrahedron Letters, 2019)
A short and efficient synthetic approach for brivaracetam has been accomplished via two different routes which utilize Pd-catalyzed oxidative cyclization and ring-closing metathesis (RCM) as the key reaction. These two routes are novel, simple, scalable and rely on (E)-pent-2-en-1-ol and valeraldehyde as a commercially available starting material to yield brivaracetam with good overall yield. (C) 2019 Published by Elsevier Ltd.
Keywords: Antiepileptic drugs; Pd-catalyzed oxidative cyclization; pyrrolinone; Ring-closing metathesis reaction

Furan-derived chiral bicycloaziridino lactone synthon: collective syntheses of oseltamivir phosphate (Tamiflu), (S)-pipecolic acid and its 3-hydroxy derivatives - Chavan, Subhash P.; Kadam, Appasaheb L.; Shinde, Shrikrishna S.; Gonnade, Rajesh G. (Chemistry-An Asian Journal, 2020)
A unified synthetic strategy for oseltamivir phosphate (tamiflu), (S)-pipecolic acid, and its 3-hydroxy derivatives from furan derived common chiral bicycloaziridino lactone synthon is described here. Key features are the short (4-steps), enantiopure, and decagram-scale synthesis of common chiral synthon from furan and its first-ever application in the total synthesis of biologically active compounds by taking the advantages of high functionalization ability of chiral synthon.
Keywords: Aziridine synthon; Chiral auxiliary; collective synthesis; Pipecolic acid; Tamiflu

Formal synthesis of (-)-quinagolide: diastereoselective ring expansion via a bicyclic aziridinium ion strategy to access the octahydrobenzo[g]quinoline architecture - Chavan, Subhash P.; Kawale, Sanket A.; Pisal, Mahesh M.; Kadam, Appasaheb L.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2021)
The diastereoselective formal synthesis of (-)-quinagolide, a D-2 receptor agonist, has been achieved. The synthesis started from L-pyroglutamic acid and relied on utilization of (a) a stereospecific catalytic hydrogenation and diastereoselective Horner-Emmons-Michael cascade to obtain functionalized prolinate, (b) a Lewis acid mediated Pummerer cyclization to construct a tricyclic fused ring system, and (c) a diastereoselective ring expansion via a bicyclic aziridinium intermediate to access the required 3-substituted piperidine scaffold.

Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine